2018
DOI: 10.6061/clinics/2018/e86
|View full text |Cite
|
Sign up to set email alerts
|

Low estrogen doses normalize testosterone and estradiol levels to the female range in transgender women

Abstract: OBJECTIVE:The ideal dosage of cross-sex hormones remains unknown. The aim of this study was to evaluate the luteinizing hormone, follicle-stimulating hormone, testosterone, estradiol and prolactin levels after low-dose estrogen therapy with or without cyproterone acetate in transgender women.METHODS:The serum hormone and biochemical profiles of 51 transgender women were evaluated before gonadectomy. Hormone therapy consisted of conjugated equine estrogen alone or combined with cyproterone acetate. The daily do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…This showed a significantly lower median serum total testosterone concentration in those treated with CPA (0.8 nmol/L), compared to spironolactone (2.0 nmol/L) and estradiol alone (10.5 nmol/L) ( P = .005 after adjustment for serum estradiol concentration, estradiol dose, spironolactone dose, CPA dose and age). In contrast, Cunha et al 20 observed a significant reduction in serum total testosterone concentrations at 6 months compared to baseline in a retrospective analysis of 51 transgender women treated with conjugated equine oestrogens (CEE) alone or with CPA 50‐100 mg daily, but no significant between‐group difference (median serum total testosterone concentration at 6 months 21 ng/dL (0.73 nmol/L) in the CPA group versus 18.0 ng/dL (0.62 nmol/L) in the CEE alone group, P = .217).…”
Section: Resultsmentioning
confidence: 88%
“…This showed a significantly lower median serum total testosterone concentration in those treated with CPA (0.8 nmol/L), compared to spironolactone (2.0 nmol/L) and estradiol alone (10.5 nmol/L) ( P = .005 after adjustment for serum estradiol concentration, estradiol dose, spironolactone dose, CPA dose and age). In contrast, Cunha et al 20 observed a significant reduction in serum total testosterone concentrations at 6 months compared to baseline in a retrospective analysis of 51 transgender women treated with conjugated equine oestrogens (CEE) alone or with CPA 50‐100 mg daily, but no significant between‐group difference (median serum total testosterone concentration at 6 months 21 ng/dL (0.73 nmol/L) in the CPA group versus 18.0 ng/dL (0.62 nmol/L) in the CEE alone group, P = .217).…”
Section: Resultsmentioning
confidence: 88%
“…Oestrogens and anti-androgens suppress serum testosterone levels and block androgen action, and it is expected that testosterone levels will decline on all forms of treatment. 26,27 Transdermal oestradiol patches or gel (and depending on availability, parenteral oestradiol injections) may be safer with regard to triglycerides and clotting risk than oral oestradiol by bypassing first-pass hepatic metabolism. 28 Transdermal oestradiol use has been proposed and implemented particularly in older TW (e.g.…”
Section: Part 1: Feminizing Gahtmentioning
confidence: 99%
“…Although there is no clear consensus, most experts agree that a physiologic estradiol range for transfeminine individuals desiring binary gender affirmation is approximately 200 pg/mL, with a commonly cited range from 80 to 250 pg/mL based on expert opinion . Agreement on physiologic testosterone level is more forthright, with a commonly cited goal of less than 55 ng/dL for binary gender affirmation .…”
Section: Gender‐affirming Hormone Therapymentioning
confidence: 99%